Tibullus 1.1.48: What Does Fire Do? - Olszaniec, Włodzimierz (Myrtia, 2025)
This note offers an emendation in Tibullus 1.1.48. It is argued that the reading iuuante transmitted by the MSS should be replaced with micante.